Exploring preconception health in adolescents and young adults: Identifying risk factors and interventions to prevent adverse maternal, perinatal, and child health outcomes-A scoping review. - Zahra Ali Padhani; Komal Abdul Rahim; Gizachew A Tessema; Jodie C Avery; Negin Mirzaei Damabi; Patience Castleton; Rehana A Salam; Salima Meherali; Zohra S Lassi (PLoS ONE)
Background Preconception health provides an opportunity to examine a woman's health status and address modifiable risk factors that can impact both a woman's and her child's health once pregnant. In this review, we aimed to investigate the preconception risk factors and interventions of early pregnancy and its impact on adverse maternal, perinatal and child health outcomes. Methods We conducted a scoping review following the PRISMA-ScR guidelines to include relevant literature identified from electronic databases. We included reviews that studied preconception risk factors and interventions among adolescents and young adults, and their impact on maternal, perinatal, and child health outcomes. All identified studies were screened for eligibility, followed by data extraction, and descriptive and thematic analysis. Findings We identified a total of 10 reviews. The findings suggest an increase in odds of maternal anaemia and maternal deaths among young mothers (up to 17 years) and low birth weight (LBW), preterm birth, stillbirths, and neonatal and perinatal mortality among babies born to mothers up to 17 years compared to those aged 19-25 years in high-income countries. It also suggested an increase in the odds of congenital anomalies among children born to mothers aged 20-24 years. Furthermore, cancer treatment during childhood or young adulthood was associated with an increased risk of preterm birth, LBW, and stillbirths. Interventions such as youth-friendly family planning services showed a significant decrease in abortion rates. Micronutrient supplementation contributed to reducing anaemia among adolescent mothers; however, human papillomavirus (HPV) and herpes simplex virus (HSV) vaccination had little to no impact on stillbirths, ectopic pregnancies, and congenital anomalies. However, one review reported an increased risk of miscarriages among young adults associated with these vaccinations. Conclusion The scoping review identified a scarcity of evidence on preconception risk factors and interventions among adolescents and young adults. This underscores the crucial need for additional research on the subject.